2020
DOI: 10.3390/ma13183910
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Oxygen Vacancy Defects in sALD-ZnO Films Annealed in Different Conditions

Abstract: Zinc oxide (ZnO) has drawn much attention due to its excellent optical and electrical properties. In this study, ZnO film was prepared by a high-deposition-rate spatial atomic layer deposition (ALD) and subjected to a post-annealing process to suppress the intrinsic defects and improve the crystallinity and film properties. The results show that the film thickness increases with annealing temperature owing to the increment of oxide layer caused by the suppression of oxygen vacancy defects as indicated by the X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 60 publications
(81 reference statements)
1
13
0
Order By: Relevance
“…The d -402 values of the annealed Ga 2 O 3 films increased from 0.23520 to 0.23596 nm with an increase in temperature from 600 to 900 • C. The release of the compressive strain causes a shifting of the diffraction peak along (-402) towards a lower Bragg angle [39], as shown in Figure 2, which increases the d-spacing in the above equation. The slope of the increase in d -402 gradually decreased with the gentle release in the compressive strain at 900 • C. The d-spacing finally approached the more standard value due to the gradual shifting of the diffraction peak along (-402) towards a lower Bragg angle under the same condition, which was possibly due to the existence of considerable point defects, including oxygen vacancy in the lattice [8,33,52]. It became necessary to examine the XPS analysis results to identify the cause of the rapid decrease in temperature.…”
Section: Resultsmentioning
confidence: 97%
“…The d -402 values of the annealed Ga 2 O 3 films increased from 0.23520 to 0.23596 nm with an increase in temperature from 600 to 900 • C. The release of the compressive strain causes a shifting of the diffraction peak along (-402) towards a lower Bragg angle [39], as shown in Figure 2, which increases the d-spacing in the above equation. The slope of the increase in d -402 gradually decreased with the gentle release in the compressive strain at 900 • C. The d-spacing finally approached the more standard value due to the gradual shifting of the diffraction peak along (-402) towards a lower Bragg angle under the same condition, which was possibly due to the existence of considerable point defects, including oxygen vacancy in the lattice [8,33,52]. It became necessary to examine the XPS analysis results to identify the cause of the rapid decrease in temperature.…”
Section: Resultsmentioning
confidence: 97%
“…For the TiO x film, the refractive index was 1.96, which is smaller than that of conventional TiO 2 film (which ranges from 2.4 to 2.75 at 550 nm) 25 . As research has shown that the refractive index can be related to the film density, we consider that a decrease in the refractive index for the prepared TiO x film implies a lower density than that of conventional TiO 2 film 26 , 27 . In the TiO x @SiO 2 NPs, the value of the refractive index decreases to 1.72, as it is affected by the embedment of the small refractive index of SiO 2 NPs (~ 1.47) 28 .…”
Section: Resultsmentioning
confidence: 99%
“…The film's refractive index increases when the annealing temperature gets between 300 -700 o C, after which the carrier concentration decreases. The V O defects are observed to be suppressed [212], and the film resistivity decreases at 800 o C. The method support deposition at a fraction of time usually used by the ALD method, high quality of deposition with high throughput, and support area-selective deposition [210]. Li et al [177] recently demonstrated how to precisely control the content of Zn and V O concentration in an ALD deposited Ga 2 O 3 /ZnO composite resistive layer via adjusting the number of the composite resistive layer cycles during the ALD power, the device shows very-low resistivity and unable to produce switching behavior (b) Device developed using 50 W RF power, the device shows an LRS that leads to its failure even with the application of the negative voltage it refused to switch to the HRS (c) Device made with RF power of 100 W (d) Device developed using RF power of 200 W. The 100 W and 200 W RF power produce devices with counter-clockwise bipolar switching characteristics [201].…”
Section: Effect Of Deposition Parametersmentioning
confidence: 94%